What Should Cognitive Science Look Like? Neither a Tree Nor Physics. (8th October 2019) - Schunn, Christian D.
Abstract: While pointing out important features of cognitive science, Núñez et al. (2019) also argue prematurely for the end of cognitive science. I discuss problematic analytic features in the application of hierarchical cluster analysis to journal citation data. On the conceptual side, I argue that the research programs framework of Lakatos may not be so wisely applied to cognitive science. Further, the diversity of structure in cognitive science departments may represent a rational, strategic adaptation by an interdisciplinary department to cognitive and other resource challenges rather than the sign of low progress on a discipline.